P047 Safety and tolerability of transcranial magnetic stimulation for motor and language mapping in children with epilepsy. Issue 3 (March 2017) - Kaye, H.L.; Gersner, R.; Oberman, L.; Chung, A.; Sanchez, M.J.; Chiriboga, N.; Boes, A.; Pascual-Leone, A.; Rotenberg, A.
Abstract : Introduction & Objectives: Transcranial magnetic stimulation (TMS) is a method for focal noninvasive cortical stimulation where small intracranial electrical currents are generated by a powerful extracranial fluctuating magnetic field. The objective of this retrospective study was to assess TMS safety and tolerability for presurgical mapping in children with epilepsy. Materials & methods: TMS was performed with a figure-of-eight coil and the site was localized to the patient's own MRI using frameless stereotaxy. Motor mapping involved single-pulse stimulation at 110% resting motor threshold (rMT), or 100% machine output (MO) when MT was ⩾100% MO. Expressive language mapping involved repetitive stimulation at 90–150% rMT, delivered in 5 Hz trains around Broca's area and the homologous right hemisphere region. Heart rate (HR) and HR variability during stimulation were extracted from the EMG as additional safety measures. Our data also enables measures of rMT as a function of age. Results: 106 patients (10 mo – 18y; 97 ⩽ 18y) with medication-refractory epilepsy underwent TMS motor mapping, and 28 patients (ages 6–18y; 24 ⩽ 18y) underwent language mapping. There were no atypical seizures, status epilepticus or epilepsy exacerbation. Typical seizures occurred in 3 patients during TMS motor mapping, and 1 seizure occurred during speech mapping. Of the three in-session seizures during motor mapping, one occurred in the setting of reduced antiepileptic medications, during EMG electrode setup, the second occurred during a session in a patient who experienced frequent daily seizures, and the third, a motor seizure with right arm extension occurred during right hand rMT determination. The seizure during language mapping may occurred in a patient with reflex audiogenic epilepsy, whose seizure were triggered by rhythmic auditory stimuli. Although higher stimulation intensity was required in younger children secondary to lower rMT the tolerability was similar in younger and older children. There was no significant change in heart rate from baseline during TMS sessions. Conclusions: Navigated TMS appears to be safe and relatively well tolerated in pediatric patients with drug-resistant epilepsy undergoing presurgical mapping.